Job Security Research in Global Perspective: A Bibliometric Mapping - Hidayat, Rahmat; Bahri, Syamsul; Pulungan, Nurhamidah (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to conduct a comprehensive bibliometric mapping of the development of the global literature on job security in the period 2020 to 2025, including publication trend analysis and keyword mapping of themes, as well as network visualization. This research is bibliometric research, where bibliometric research is a systematic study conducted on the scientific literature to identify, explore, analyze patterns, trends, and impacts in certain fields. Search the article database on the Google Scholar page using Publish or Perish (PoP) software. The method of searching and selecting documents based on